Перспективи розвитку туристичної інфраструктури Маневицького району Волинської області - Чир, Надія Вікторівна; Єрко, Ірина Володимирівна; Качаровський, Роман Євгенович; Антипюк, Олена Володимирівна; Chyr, Nadiia V.; Yerko, Iryna V.; Kacharovskyi, Roman Ye.; Antypiuk, Olena V. (Тернопільський національний педагогічний університет імені Володимира Гнатюка, 2018)
Здійснено комплексну оцінку можливостей розвитку туристичної інфраструктури Маневицького району Волинської області. Основне завдання статті – визначення рівня розвитку туристської інфраструктури Маневицького району та її ролі у формуванні основних засад економічного розвитку району. Проаналізовано наукові дослідження із даної тематики. Охарактеризовано суспільно-географічне положення району. Досліджено природно-ресурсний потенціал. Охарактеризовано суспільно-історичні рекреаційно-туристичні ресурси. Досліджено елементи туристичної інфраструктури району, а саме: заклади тимчасового розміщення, харчування, дозвілля та побутового обслуговування, транспортної інфраструктури, зв’язку та інформаційного забезпечення, визначено їх коефіцієнти забезпеченості. Визначено основні проблеми структурних елементів туристської інфраструктури, запропоновано можливі шляхи їх вирішення. Охарактеризовано проблемні питання, що постають у розвитку галузі туризму. Визначено першочергові заходи покращення туристської інфраструктури району. Подано висновки та перспективи подальших досліджень.

Complex evaluation of the opportunities of tourism infrastructure development in Manevychi district of Volyn region was realized. The main task of the article is to determine the level of the tourism infrastructure development in Manevychi district and its role in forming of the main principles of economic development of the district. Scientific researches of this themes were analyzed. Socially-geographical location of the district was described. It was researched the naturally-resourceful potential. Socially-historical, recreational and tourist resources were characterized. It was researched the elements of tourism infrastructure in district namely: establishments of temporary accomodation, nutrition, leasure and everyday serving, transport infrastructure, communication and providing with information and the coefficients of their providing were determined. Main problems of srtuctural elements of tourism infrastructure were determined and possible ways of its solution were offered. Problem questions arising in tourism development were characterized. Immediate measures of tourism infrastructure improvement in district were determined. Conclusions and prospects of further research were given. The advantageous geographical location of the Manevitsky district contributes to the development of tourist infrastructure, which accordingly increases the share of tourism as an industry in the region's economy. The degree of formation of the tourist infrastructure of the district is quite significant, although each link requires a separate, integrated, systematic approach to improving, reforming and developing the infrastructure of tourist services at the proper European level. In the process of transformation, the latest trends in the development of the tourism industry with the use of modern nanotechnologies and information systems should be used, which will allow, in the short term, to ensure long-term financial stability and address a number of social problems in the area.
Prospects of development of the tourism infrastructure in Manevychi district of Volyn Region
Keywords: туризм; туристська інфраструктура; Маневицький район; Волинська область; заклади тимчасового розміщення; заклади ресторанного господарства; tourism; tourism infrastructure; establishments of temporary accomodation; establishments of restaurant economy; Manevychi district; Volyn region